Prevalence of asymptomatic bacteriuria in pregnant women (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Women with asymptomatic bacteriuria during pregnancy are more likely to deliver premature or low birth weight babies and having a 20 40 percent increased risk of developing pyelonephritis during pregnancy compared with women without bacteriuria. Asymptomatic bacteriuria is a microbiological diagnosis based on urine culture from persons without signs or symptoms of urinary tract infection. Objectives: The aim of this study was to determine the prevalence of asymptomatic bacteriuria in pregnant women and also to determine the relationship between the asymptomatic bacteriuria and pyuria to isolate the causative pathogens and to find out the antimicrobial susceptibility pattern of the isolates. Methods: A total of 540 urine specimen were collected from 540 asymptomatic pregnant women for urinary tract infection, over a period 2 years from January 2011 to December 2012 at Border Guard Bangladesh (BGB) Hospital, Pilkhana, Dhaka. All specimens were processed using standard microbiological procedures. All the subjects were evaluated for bacteriuria. Results: The prevalence of asymptomatic bacteriuria was 10.2% . Pyuria was found in 15.9% of cases. Escherichia coli (80%) was the commonest causative agent of asymptomatic bacteriuria followed by Staphylococcus saprophyticus (14.5%) and Pseudomonas spp.(5.5%). Nitrofurantoin was found to be highly sensitive to most of the isolates. 64 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Conclusion: Screening for bacteriuria in pregnancy and proper treatment of diagnosed cases must be considered as an essential part of antenatal care in our country. To prevent complications of asymptomatic bacteriuria, all pregnant women should be screened at the first antenatal visit. A negative test for pyuria is not a reliable indicator of the absence of asymptomatic bacteriuria in pregnant women. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21830 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013